2016
DOI: 10.1186/s13071-016-1692-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plasmodium falciparum isolates from uncomplicated malaria cases in Ghana over a decade

Abstract: BackgroundGenotyping malaria parasites to assess their diversity in different geographic settings have become necessary for the selection of antigenic epitopes for vaccine development and for antimalarial drug efficacy or resistance investigations. This study describes the genetic diversity of Plasmodium falciparum isolates from uncomplicated malaria cases over a ten year period (2003–2013) in Ghana using the polymorphic antigenic marker, merozoite surface protein 2 (msp2).MethodsArchived filter paper blood bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 38 publications
5
30
3
Order By: Relevance
“…MOI was also found to be significantly higher in the wet season compared with the dry season at the nondam site (p � 0.0002) but not at the dam site (Table 3). ese data agree with the report by Duah et al [33] who found similar MOI in the Savannah regions of Ghana. Although this study did not directly assess the levels of gametocytes and malaria transmission by the vector, there are published reports of a direct correlation between MOI and transmission intensity [35], and the higher dam site MOI could mean a higher extent of transmission at this site during the dry season compared with the nondam site.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MOI was also found to be significantly higher in the wet season compared with the dry season at the nondam site (p � 0.0002) but not at the dam site (Table 3). ese data agree with the report by Duah et al [33] who found similar MOI in the Savannah regions of Ghana. Although this study did not directly assess the levels of gametocytes and malaria transmission by the vector, there are published reports of a direct correlation between MOI and transmission intensity [35], and the higher dam site MOI could mean a higher extent of transmission at this site during the dry season compared with the nondam site.…”
Section: Discussionsupporting
confidence: 92%
“…e study showed a moderate-to-high P. falciparum allelic diversity with the 3D7 allelic family being the most predominant variant circulating in the study communities ( Figure 2). is is similar to data reported from other regions of Ghana and countries in sub-Saharan Africa with similar malaria transmission settings [29,[31][32][33]. A study conducted in the south of Benin however reported the FC27 family as the most predominant allelic family [34].…”
Section: Discussionsupporting
confidence: 89%
“…Fertilization between two distinct parasites provides the opportunity for chromosome recombination during meiosis, which enhances genetic diversity in the parasite population. Geometric mean MOIs for msp1 and msp2 of 1.90 and 1.88 were slightly lower than obtained in an earlier report from the middle belt of Ghana where MOI was 2.3 in July/August, [52] but similar to another report of MOI in southern Ghana which was 1.93 [24] and 1.3 in 2013 [53]. This discrepancy may be due to differences in ecological zones [54], malaria transmission intensity [36, 55] and/or the treatment-seeking behaviour of malaria patients within the various population [56, 57].…”
Section: Discussionsupporting
confidence: 73%
“…However, this study identified the 3D7 allele of msp2 as the most prevalent (Fig. 2 ), which was contrary to our previous study [ 28 ] but similar to other studies conducted in Ghana [ 33 , 34 ].…”
Section: Discussioncontrasting
confidence: 71%